Efektifitas Bahan Pengawet Dari Asap Cair Tandan Kosong Kelapa Sawit (Elaeis guineensis) Terhadap Serangan Rayap (Coptotermes curvignathus Holmgren) Pada Kayu Pulai (Alstonia scholaris) - Sulaeman, Rudianda; Sribudiani, Evi; ', Annahyan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Pulai wood have economic value, while durable grade is V and powerful class is IV-V and it is low-grade durable, because of that it is needed preservation on Pulai wood. Many Preservation using chemicals that are harmful to environment and humans. In utilizing natural ingredients derived from plants as safer alternative preservatives for environment and humans, it can be renewable for preserving wood from invading organisms wood destroying, especially termites. Materials used as a preservative is liquid smoke empty fruit bunches of oil palm. The aims of this research are to determine termite mortality, retention, weight lose, and water content as well as know the effectiveness of the provision of liquid smoke on Pulai wood preservation against termite attack. The methods used in this research is (RAL), the concentration of liquid smoke oil palm empty fruit bunches of 0%, 10%, 20%, and 30% with 5 replications for three weeks is fed on termites. The results showed that using of preservatives smoke liquid at concentrations of 30% has a value of lose weight on Pulai wood of 0.00g/cm3 and 100% termite mortality. Key word: Liquid Smoke, TKKS, Preservative, Pulai Wood And Coptotermes CurvignathusÂ Â  Holmgren.